Specific determination of hepatitis B e antigen by antibodies targeting precore unique epitope facilitates clinical diagnosis and drug evaluation against hepatitis B virus infection - Shao-Juan Wang; Zi-Min Chen; Min Wei; Jia-Qi Liu; Zong-Lin Li; Tian-Shu Shi; Sheng Nian; Rao Fu; Yang-Tao Wu; Ya-Li Zhang; Ying-Bin Wang; Tian-Ying Zhang; et al. (Emerging Microbes and Infections)
Hepatitis B e antigen (HBeAg) is a widely used marker both for chronic hepatitis B (CHB) clinical management and HBV-related basic research. However, due to its high amino acid sequence homology to hepatitis B core antigen (HBcAg), most of available anti-HBe antibodies are cross-reactive with HBcAg resulting in high interference against accurate measurement of the status and level of HBeAg. In the study, we generated several monoclonal antibodies (mAbs) targeting various epitopes on HBeAg and HBcAg. Among these mAbs, a novel mAb 16D9, which recognizes the SKLCLG (aa −10 to −5) motif on the N-terminal residues of HBeAg that is absent on HBcAg, exhibited excellent detection sensitivity and specificity in pairing with another 14A7 mAb targeting the HBeAg C-terminus (STLPETTVVRRRGR, aa141 to 154). Based on these two mAbs, we developed a novel chemiluminescent HBeAg immunoassay (NTR-HBeAg) which could detect HBeAg derived from various HBV genotypes. In contrast to widely used commercial assays, the NTR-HBeAg completely eliminated the cross-reactivity with secreted HBcAg from precore mutant (G1896A) virus in either cell culture or patient sera. The improved specificity of the NTR-HBeAg assay enables its applicability in cccDNA-targeting drug screening in cell culture systems and also provides an accurate tool for clinical HBeAg detection.